Influence of paternal and maternal ethnicity and ethnic enclaves on newborn weight - Zipursky, Amy R; Park, Alison L; Urquia, Marcelo L; Creatore, Maria I; Ray, Joel G (Journal of epidemiology and community health (1979), 2014)
Background The association between maternal ethnicity and newborn weight is understood. Less is known about the additional influence of paternal ethnicity and neighbourhood ethnic composition. Methods We studied 692 301 singleton live births of parents of Canadian, Bangladeshi, Sri Lankan, Pakistani, Indian, Filipino, Vietnamese, Korean, Hong Kong or Chinese birthplace. We used multivariable regression to calculate mean (95% CI) birthweight differences between infants of two Canadian-origin parents and (1) foreign-born mother and Canadian-born father, (2) Canadian-born mother and foreign-born father or (3) two foreign-born parents from the same country. We also stratified by high versus low same-ethnic concentration of the parent’s residence. We adjusted for gestational age at birth, maternal age, parity, marital status and income quintile. Results Compared with male and female infants of two Canadian-born parents, those of same-country foreign-born parents weighed 6.2% (−218 g, 95% CI −214 g to −223 g) and 5.6% (−192 g, 95% CI −187 g to −196 g) less, respectively. The largest mean weight difference was among male (8.4% (−297 g, 95% CI −276 g to −319 g)) and female (8.2% (−279 g, 95% CI −262 g to −296 g)) infants of two Bangladeshi parents. Infants of a foreign-born mother and Canadian-born father had weights closest to those of two Canadian-born parents. Residing in an area of high (vs low) same-ethnic concentration was associated with lower birthweight among infants of mixed union couples, but not among those of parents originating from the same country. Conclusions Paternal and maternal ethnic origin influence newborn weight, which is modified by settlement in a high same-ethnic concentration area only among parents of mixed union.